Texture and mouthfeel perceptions of a model beverage system containing soluble and insoluble oat bran fibres. (June 2019) - Chakraborty, Piyali; Witt, Torsten; Harris, David; Ashton, John; Stokes, Jason R.; Smyth, Heather E.
Abstract: Dietary fibre fortified products have increased in popularity as health-conscious consumers seek convenient ways to increase fibre intake. Fibres from wholegrains are particularly desirable inclusions in food products because of their proven physiological health-benefits. When fortifying beverages with fibre, however, the insoluble dietary fibre components present in wholegrains often contribute to unpleasant gritty sensations making the products unpalatable. Consequently, designing wholegrain-fortified beverages with sufficient fibre-content to make health related fibre claims is a major challenge in the food manufacturing industry. This work aims to take a systematic approach in identifying the texture/mouthfeel related sensory impact and interaction between two commercial oat fibre ingredients (Oatwell28XF® and Milled Oats) when added to a model beverage system. Eighteen samples were prepared containing either or both the ingredients, at varying levels, and were assessed by a trained panel using conventional sensory descriptive techniques. The results indicate that the two different oat bran fibres produced distinct mouthfeel perceptions which could be attributed to the varying soluble and insoluble fibre content of the samples. Insoluble dietary fibre concentrations above 2% (w/w) resulted in particle-related sensory properties chalkiness, dryness and particle perception, which dominated the overall mouthfeel and textural sensory perception of the samples. Samples with predominantly soluble β-glucan, resulted in perceptions of smoothness, sliminess and stickiness residue, while thickness, mouthcoating and cloying sensations were driven by total fibre concentration, irrespective of fibre solubility. This work provides a solid foundation for food manufacturers aiming to rationally design and develop nutritionally superior fibre-fortified beverages and is relevant to fibre content concentrations required for labelling/nutrition claims for consumer products in many developed nations. Graphical abstract: Unlabelled Image Highlights: A systematic approach allowed for a rational investigation of the sensory interaction between soluble and insoluble fibres in a model beverage matrix. Samples with added Oatwell28XF®, predominantly soluble β-glucan, resulted in perceptions of smoothness, sliminess and stickiness residue. Samples with added Milled Oats bran, predominantly comprising insoluble cellulosic fibres, resulted in particle perception, chalkiness and dryness. Sensory attributes thickness, mouthcoating and cloying were driven by total fibre concentration, irrespective of fibre solubility. The sensory threshold for insoluble fibre particle perception was just below 2% (w/w) insoluble dietary fibre in the model beverage matrix.